Impact of radiation dose and iterative reconstruction (IR) level on low-contrast detectability with 4-AFC approach (International Journal of Scientific Research in Science and Technology, 2024)
This study evaluated impacts of dose and iterative reconstruction (IR) level on low-contrast detectability in images of AAPM CT Performance phantom using a 4-alternative forced choice (4-AFC) approach. Five medical physicists detected low-contrast and small objects having size of 3.0 mm with the 4-AFC method. The tests were conducted at three different radiation doses (35.8 mGy, 54.1 mGy, and 72.1 mGy) at various IR levels from 0% to 100%. The total number of 4-AFC questions was 330 questions in which each observer answered the questions in 60 minutes. Percent correct answers increase as the IR level increases from 0 to 100%. The percent correct answers also increase as the dose increases from 34.8 mGy to 72.1 mGy. 100% correct answers start at IR levels of 70, 60, and 40% for doses of 34.8, 54.1, and 72.1 mGy, respectively. Conclusions: Increasing IR level and dose improve image quality, i.e., higher average percent correct answers. At IR levels around 50%, the average percent correct is close to the maximum (around 100%) for all radiation doses. An optimal combination of IR and radiation dose can produce good image quality with lower radiation dose.
Keywords: Iterative reconstruction; radiation dose; low-contrast detectability; 4-AFC; image quality